George Henry Somerset Walpole correspondence - Walpole, George Henry Somerset, 1854-1929.
Letter of appreciation addressed to Cordelia Jackson.
Anglican bishop of Edinburgh, Scotland.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Jackson, Cordelia -- Correspondence; Clergy